Early Menarche is a Risk Factor for Short Stature in Young Korean Females: An Epidemiologic Study - Sol Kang; Yoon Mo Kim; Jun Ah Lee; Dong Ho Kim; Jung Sub Lim (JCRPE, 2019)

(untitled)
Objective:To assess the association between age at menarche and adult height [and body mass index (BMI)] in young Korean females and also to investigate whether early menarche (<12 years) is a risk factor for short stature and obesity in young Korean females.Methods:Data on 1148 females aged 18-30 years and 612 mother (612 pairs of mothers and daughters) from the 6th Korea National Health and Nutrition Examination Survey (2013-2015) were analyzed.Results:Among 1148 females, 256 (22.3%) had early menarche. Their stature was approximately 0.445 cm shorter when menarche had occurred one year earlier. The prevalence of short stature (≤153 cm) and obesity (BMI ≥25) was higher in females with early menarche compared to those with later menarche (short stature: 10.5% vs 6.4%, obesity; 20.7% vs 13.1%, all p<0.001). In multivariate regression, the odds ratio (OR) for short stature was 2.62 [95% confidence interval (CI): 1.26-5.44] after adjusting for current age and mother’s height. OR for obesity was 1.74 (95% CI: 0.98-3.07) after adjusting for age and maternal BMI.Conclusion:Final height in girls is influenced by age of menarche. Early menarche increased the risk for adult short stature in young Korean females.